2015
DOI: 10.1002/mpr.1467
|View full text |Cite
|
Sign up to set email alerts
|

What does the beck depression inventory measure in myocardial infarction patients? a psychometric approach using item response theory and person‐fit

Abstract: Observed associations between depression following myocardial infarction (MI) and adverse cardiac outcomes could be overestimated due to patients' tendency to over report somatic depressive symptoms. This study was aimed to investigate this issue with modern psychometrics, using item response theory (IRT) and person-fit statistics to investigate if the Beck Depression Inventory (BDI) measures depression or something else among MI-patients. An IRT-model was fit to BDI-data of 1135 MI patients. Patients' adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 53 publications
1
31
1
2
Order By: Relevance
“…However, the authors did not attempt to account for the role of physical health in their results. Wardenaar et al performed a similar IRT analysis of the BDI in subjects postmyocardial infarction and found that mood items were more representative of diagnosed depression, compared to somatic items, which were reported frequently in all subjects [16]. Collectively, these analyses support the use of IRT to better understand the effect of medical comorbidity on the assessment of depression.…”
Section: Introductionmentioning
confidence: 84%
“…However, the authors did not attempt to account for the role of physical health in their results. Wardenaar et al performed a similar IRT analysis of the BDI in subjects postmyocardial infarction and found that mood items were more representative of diagnosed depression, compared to somatic items, which were reported frequently in all subjects [16]. Collectively, these analyses support the use of IRT to better understand the effect of medical comorbidity on the assessment of depression.…”
Section: Introductionmentioning
confidence: 84%
“…Foremost, a baseline model was estimated including only the control variables: IDS total score (e.g. Conijn et al, ; Wanders al., ; Wardenaar et al, ) and dummy variables representing the data collection waves. Next, extended models were estimated by including either a block of atypical symptom profiles, or a block of explanatory variables related to the quality of the self‐report.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that person‐fit statistics could be used to screen for atypical suicide risk. Wardenaar et al () found that person misfit on the Beck Depression Inventory in a sample of myocardial infarct patients reflected an atypical symptom profile characterized by low somatic complaints but other depressive symptoms indicative of clinical levels of depression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations